Axial position estimation of conical shaped motors for aerospace traction applications - Roggia, S.; Cupertino, Francesco; Gerada, C.; Galea, Michael (IEEE, 2017)
This paper is concerned with the use of conical induction machines. Such machines are extremely valuable when apart from the rotational torque output, an axial translation of the rotor is also required. The inherent attraction between the stator and rotor of any machine, combined with the geometry of a conical machine will provide the required axial movement. However, when applied to aerospace applications, where reliability is very important, then full monitoring of the axial position is required. In this paper, an innovative approach aimed at monitoring and controlling the axial translation of a conical induction machine is proposed and investigated. In order to increase the system reliability and also decrease component count, as demanded by the application, the methodology is a sensor-less technique, based on an innovative variant of the high-frequency injection approach. In this paper, the technique has been fully investigated and experimentally validated on a purposely-built, instrumented test-rig.